Optimization of turbulent air jet impingement for energy efficient commercial cooking. (February 2019) - Shevade, Shantanu; Rahman, Muhammad; Guldiken, Rasim
Abstract: Thermally balancing and optimizing performance of conveyor ovens is a complicated problem requiring a thorough understanding of multiple turbulent air jet impingement. A 3D model of a conveyor oven is created. Number of high impact parameters are varied through a systematic approach. Velocity distribution and air leakage from the oven to surrounding air is analyzed to optimize energy consumption. Surface heat flux and heat transfer coefficient are studied. Through process of optimization, an oven configuration is selected which is expected to perform 20% better than the starting configuration.